Comparison of Different Types of Bleaching Earth on the Quality of Bleaching Palm Oil (BPO) - Khairati, Miftahul; Aini, Apsari Puspita; Nurmalasari, Enny; Yahya, Agung Kurnia (Eksergi, 2025)
Bleaching Earth (BE), primarily derived from Bentonite, is widely used in the bleaching process of Crude Palm Oil (CPO). Its efficiency depends on the proportions of SiO₂ and Al₂O₃, which enable effective pigment absorption. This study evaluates the performance of unmodified Bentonite, nano SiO₂-modified Bentonite, and commercial BE in producing Bleached Palm Oil (BPO). The novelty lies in the nano SiO₂ modification, designed to enhance the structural properties and absorption capabilities of Bentonite. Characterization of BE was conducted using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM), while BPO quality was assessed through parameters like moisture content, acid value, Free Fatty Acid (FFA) levels, (Deterioration of Bleachability Index (DOBI), and β-carotene concentration. The results showed that BPO processed with nano SiO₂-modified Bentonite had the lowest β-carotene concentration (443%) and a DOBI value of 1.453, demonstrating superior bleaching performance compared to unmodified and commercial BE. Other parameters, including FFA levels and moisture content, exhibited minimal variation. Color analysis revealed that BPO processed with nano SiO₂-modified Bentonite achieved a comparable color value (1.5/15) to commercial BE. These findings highlight the potential of nano SiO₂-modified bentonite for improving oil quality by reducing FFA and acid value while maintaining optimal moisture content, offering a novel and effective alternative to unmodified bentonite in oil refining.